PD-1/L1 inhibitor plus chemotherapy in the treatment of sarcomas - Tian, Zhichao; Yao, Weitao (Frontiers in Immunology, 2022)
There is an urgent clinical need for new therapeutic regimens for the effective treatment of advanced sarcomas. Accumulating evidence suggests that programmed death receptor-1/programmed death protein ligand-1 (PD-1/L1) inhibitors have synergistic effects with chemotherapy and have been approved for treatment of lung cancer, gastroesophageal cancer, and breast cancer. In this review, we reviewed the synergistic mechanism of PD-1/L1 inhibitors plus chemotherapy in the treatment of cancers, and the application of this combined regimen in several cancers, followed by a summary of the current evidence on the application of this combined regimen in the treatment of sarcomas as well as the main clinical trials currently underway. Based on the findings of this review, we believe that this combined approach will play an important role in the treatment of some subtypes of sarcomas in the future.